In-vivo and In-silico analysis of the anti-inflammatory, antipyretic, and analgesic activities of methanolic fruit extracts of Carica papaya - Zahra, Nureen; Mushtaq, Iqra; Rehman, Abdul; Fatima, Saher; Khalid, Areej; Sarwar, Abid; Ullah, Najeeb; Aziz, Tariq; Alhomrani, Majid; Alsanie, Walaa F.; Alamri, Abdulhakeem S. (Italian Journal of Food Science, 2024)
Recently, the researchers are focused on the biotherapeutic properties of medicinal as well as edible plants. Inflammation, fever, and pain are common symptoms associated with various diseases, necessitating effective therapeutic potentials for relief and healing. This study aimed to assess the therapeutic impact and mechanisms of action of the methanolic fruit extract of Carica papaya for anti-inflammatory, antipyretic, and analgesic activities via in-vivo and in-vitro approaches. For inducing inflammation, pain, and fever in albino rats, carrageenan, acetic acid dilution in distilled water, and yeast dilution in saline were used. The four different concentrations (50, 100, 200, and 400 mg/kg) of methanolic extract of C. papaya fruit were used to prevent inflammation, pain, and fever. Diclofenac and paracetamol were used as standard drugs in this study. The methanolic extract of C. papaya fruit showed efficient antipyretic and anti-inflammatory inhibition (90 and 80%, respectively), but less efficient analgesic inhibition (36%). Similarly, the in-silico study used fruit bioactive compounds such as quercetin as ligand molecules, and proteins for anti-inflammatory and antipyretic activities were 1bp4 and 4x37, respectively. The docking process was done using ligand and protein molecules. The results of the in-silico study were the same as those of the in-vivo study; anti-inflammatory and antipyretic activity binding energy values were more efficient than those of an analgesic. In conclusion, the methanolic extract of C. papaya fruit in in-silico and in-vivo studies proved less efficient against pain and more efficient against inflammation and fever.